Hubungan Antara Pendidikan Seksual Yang Didapat Melalui Orang Tua, Peer Group dan Media Massa Dengan Perilaku Seksual Remaja : Studi Kasus Pada SMU "X" Jakarta - Handayani, Dini (Jurnal Ilmu Kesejahteraan Sosial, 2006)
Adolescent’s sexual behavior can be controlled to be inactive by providing sexual education to them. From 215 adolescenst,63.3% seldom receive sexual education from their parent. There’s 76.7% respondents get sexual education through peer group. 68.8% respondent admits that receive frequent sexual education through mass media. There’re 77.7% respondents are sexually inactive. Liveliness depends on various activities and also its intensity. There’re 22.3% respondents never having courtship. 3.3% respondents, who have motived in courtship, have sexual activity before married. From relation between variables, the respondents who seldom receive sexual education have possibility consider 0.83 more sexually active than the respondents who receive